The Level of Trust of Young Catholics in the Institutional Representatives of the Catholic Church: An Example from Poland - Adam R. Szromek; Grzegorz Polok; Marek Bugdol (Religions)
The article addresses the issue of the level of trust in the Catholic clergy in Poland among the youngest adult Catholics. The authors formulate their conclusions on the basis of a literature review and their own extensive research conducted among young adult Catholics born after 1995 (Generation Z). The research focused on the level of trust assessed with regard to the hierarchical division of the clergy in the Catholic Church as well as scandals involving priests exposed in recent years. The performed analyses took into account the level of religious commitment of young Catholics and their attitudes towards the role of the hierarchical Church in solving their problems. The research results indicate a significant level of trust in the Pope, a slightly lower level of trust in parish priests, and a very low level of trust in bishops and the institution of the Catholic Church in general. The decisive majority of those following religious observances and declaring compliance with the moral principles in line with Church teachings maintain trust in the institution of the Church. The final conclusions point to the need to manage the trust of the faithful as beneficiaries and clients of religious organisations such as the Church.